Dysregulated sphingolipid metabolism and autophagy in granulosa cells of women with endometriosis - Turathum, Bongkoch; Gao, Er-Meng; Grataitong, Khwanthana; Liu, Yu-Bing; Wang, Ling; Dai, Xue; Chian, Ri-Cheng (Frontiers in Endocrinology, 2022)
We evaluated metabolic profiles between cumulus cells (CCs) and mural granulosa cells (MGCs) derived from women with endometriosis to identify their correlations with oocyte quality. CCs and MGCs were collected from women with and without endometriosis undergoing in vitro fertilization/intracytoplasmic sperm injection treatment. The metabolomics of CCs and MGCs were measured by liquid chromatography coupled to tandem mass spectrometry (LC-MS/MS) followed by a quantitative polymerase chain reaction to further confirm the genes involved in the metabolic results. LC-MS/MS analysis revealed differences in 24 metabolites of CCs and 71 metabolites of MGCs respectively between groups. Among them, five metabolites were upregulated and 19 metabolites were downregulated in CCs with endometriosis, whereas three metabolites were upregulated and 68 metabolites were downregulated in MGCs with endometriosis. Metabolites related to sphingolipid metabolism, which included palmitic acid (PA) and docosahexaenoic acid, increased significantly only in CCs with endometriosis, whereas sphingosine and PA were signiﬁcantly downregulated in MGCs with endometriosis compared with CCs and MGCs without endometriosis. Gene expression involved in ceramide synthesis (CERS1, SPTL1, and SMPD1) and autophagy (BECN1, LAMP, and PC3) were significantly higher in CCs with endometriosis according to FASN, BECN1, and LAMP protein expressions. However, gene expression involved in ceramide synthesis (SPHK1, ASAH1, and SGPP1) and autophagy (BECN1, LAMP, and PC3) were significantly lower in MGCs with endometriosis, whereas CERS1 and UGCG expression increased. There are differences in sphingolipid metabolites in CCs and MGCs with endometriosis compared with women without endometriosis. These differences seem to be involved in the regulation of autophagic cell death in preovulatory follicles.